Cerebral Phaeohyphomycosis Caused by Rhinocladiella mackenziei in a Woman Native to Afghanistan - Cristini, Alejandro (American Society for Microbiology (ASM), 2010)
Rhinocladiella mackenziei is a recognized cause of endemic cerebral phaeohyphomycosis in the Middle East area. Surgical resection of the abscesses and posaconazole treatment have improved the ominous prognosis of this disease. We describe the case of a native Afghan woman living in France who presented with brain abscesses due to R. mackenziei.